The Overview of Monitoring Drug Therapy in Type 2 Diabetes Mellitus Patients at the Inpatient Pharmacy Installation of Tk. III Dr. R. Soeharsono - Nazhipah Isnani (Jurnal Kajian Ilmiah Kesehatan dan Teknologi, 2022)
Diabetes Mellitus (DM) is one of the most important public health problems and is one of the four non-communicable diseases that are government priorities. Drug Therapy Monitoring (PTO) is a process that includes activities to ensure safe, effective and rational drug therapy for patients. The purpose of this study was to describe the suitability of the implementation of PTO with the Regulation of the Minister of Health of the Republic of Indonesia (Permenkes) Number 72 of 2016 concerning Pharmaceutical Service Standards in Hospitals and to describe PTO activities in type 2 DM patients in the inpatient pharmacy installation of the Tk. III Dr. R. Soeharsono. This study is a descriptive study with retrospective data collection using the PTO form and medical records of inpatients during the period January – December 2020 at Tk Hospital. III Dr. R. Soeharsono. The results showed the suitability of the implementation of PTO by pharmacists based on standards was 100%. The number of patients studied were 96 patients. profile of potential drug interactions in clinical categories, namely contraindications, serious, monitoring, and minor. Profile of potential drug interactions in hospitalized patients based on gender, age, number of drugs and number of diseases. PTO activities are carried out by pharmacists for inpatients with the main characteristics of patients experiencing disease complications. All PTO activities are carried out based on the number and ability of pharmacists Keywords : Monitoring drug therapy, Type 2 Diabetes Mellitus